2023
DOI: 10.31393/reports-vnmedical-2023-27(2)-07
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of arginine glutamate on cognitive processes in food-deprived rats

Abstract: Annotation. In 2022, due to the COVID-19 pandemic and the aggravation of the food crisis, as a result of the full-scale Russian invasion of Ukraine, the share of the world's starving population has increased to 9.8% of the world's population. According to the literature, metabolic and neuroendocrine disorders during starvation have a negative impact on cognitive processes and social behavior. The aim of the study was to justify experimentally the feasibility of using glutargin for the correction of cognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…J. Kumar et al [5] have hypothesized that L-Glu may enhance the antioxidant status and affect the concentration of neurotransmitters. The positive effect of glutamic acid, both alone and in combination with other substances, has also been established in the treatment of nutritional deficiencies [6,7]. L.A. Ponomarenko et al [8] found that the use of drug based on glutamic acid in the basic therapy of patients with gastroenterological pathology has increased the level of reduced glutathione and normalized lipoperoxidation processes.…”
Section: Resultsmentioning
confidence: 99%
“…J. Kumar et al [5] have hypothesized that L-Glu may enhance the antioxidant status and affect the concentration of neurotransmitters. The positive effect of glutamic acid, both alone and in combination with other substances, has also been established in the treatment of nutritional deficiencies [6,7]. L.A. Ponomarenko et al [8] found that the use of drug based on glutamic acid in the basic therapy of patients with gastroenterological pathology has increased the level of reduced glutathione and normalized lipoperoxidation processes.…”
Section: Resultsmentioning
confidence: 99%